Local coupling and conversion of surface waves due to Earth's rotation. Part 2: numerical examples. Issue 1 (12th December 2020) - Sens-Schönfelder, Christoph; Bozdağ, Ebru; Snieder, Roel
SUMMARY: Rotation of the Earth affects the propagation of seismic waves. The global coupling of spheroidal and toroidal modes by the Coriolis force over time is described by normal-mode theory. The local action of the Coriolis force on the propagation of surface waves can be described by coefficients for the coupling between propagating Rayleigh and Love waves as derived by Snieder & Sens-Schönfelder. Usin6g global wavefield simulations we show how the Coriolis force leads to coupling and conversion between both surface wave types depending on latitude, propagation direction, frequency, and local velocity structure. Surface wave coupling is most efficient for periods where the modes have similar phase velocities, a condition that is equivalent to the selection rules of the angular degree in the normal-mode framework, a phenomenon that we refer to as resonant coupling . In the time-domain, resonant coupling gradually converts energy from one wave type—Rayleigh waves or Love wave—into the other, which then propagates independently. Due to the lateral heterogeneity, the condition of equal phase velocity renders the rotational coupling location-dependent. East–west oriented ray path segments and segments at high latitudes (across the Poles) only weakly couple the fundamental mode Rayleigh and Love waves while coupling is strongest for propagation along the meridians across the equator. At 250 s period, where Love and Rayleigh waves have similar phase velocities, the net energy transfer from Rayleigh to Love wave reaches about 10 per cent for one orbit.